1999
DOI: 10.1016/s1388-9842(98)00004-x
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐blocker therapy in advanced heart failure: clinical characteristics and long‐term outcomes

Abstract: Aims: To evaluate the clinical characteristics and long-term outcomes of advanced heart failure patients (NYHA Class IIIb-IV) receiving beta-blocker therapy vs. those patients not receiving beta-blockers at randomization in the FIRST trial, a randomized, double-blind, placebo-controlled trial of epoprostenol vs. usual care in advanced heart failure. Methods and results: The patient population consisted of 471 patients enrolled in FIRST with Class IIIb-IV heart failure, left ventricular ejection fraction (LVEF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…A secondary analysis of the Outcomes of a Prospective Trial of Intravenous Milrinone for Exacerbations of Chronic Heart Failure (OPTIME-CHF) study by Gattis et al (9) suggested that beta-blocker discontinuation during hospitalization was associated with a higher mortality rate after discharge within 60 days. Similarly, a retrospective analysis of the Flolan International Randomized Survival Trial (FIRST) database assessed clinical outcomes related to beta-blocker use at randomization and reported no excess risk for patients treated with beta-blockers at the time of hospital presentation (10). In this investigation, we assessed this issue using the ESCAPE trial database and found that continuation of beta-blocker therapy, even after adjusting for potential confounders associated with beta-blocker use or the outcomes studied, was associated with a lower mortality and rehospitalization rate subsequent to discharge.…”
Section: Discussionmentioning
confidence: 99%
“…A secondary analysis of the Outcomes of a Prospective Trial of Intravenous Milrinone for Exacerbations of Chronic Heart Failure (OPTIME-CHF) study by Gattis et al (9) suggested that beta-blocker discontinuation during hospitalization was associated with a higher mortality rate after discharge within 60 days. Similarly, a retrospective analysis of the Flolan International Randomized Survival Trial (FIRST) database assessed clinical outcomes related to beta-blocker use at randomization and reported no excess risk for patients treated with beta-blockers at the time of hospital presentation (10). In this investigation, we assessed this issue using the ESCAPE trial database and found that continuation of beta-blocker therapy, even after adjusting for potential confounders associated with beta-blocker use or the outcomes studied, was associated with a lower mortality and rehospitalization rate subsequent to discharge.…”
Section: Discussionmentioning
confidence: 99%
“…The study results indicating favorable effects of heart failure therapy using β‐blockers in functional class IV were published very recently [30] while the favorable effects of β‐blockade in heart failure in general have been published in 1989 and thereafter [31]. However, the proportion of functional class IV with the rural hospital patient group was as high as 69%, which might at least partially explain the lower β‐blocker use in that particular patient group.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike chronic heart failure (CHF), for which a wealth of information is available, specific epidemiological data on ADHF are currently lacking. Indeed, available data are non‐specific, and usually derived from hospital discharge records corresponding to the general heart failure code [ICM 184] [3–5] as well as from a limited number of recent large clinical trials in patients with worsening heart failure [6–9].…”
Section: Introductionmentioning
confidence: 99%